Synthesis and Antifungal Activity of Some 2-Arylimino-3- Phthalimidoacetyl-4-Thiazolidinones and Their 5-Arylidine Derivatives - Sah, M.M.; Joshi (Jr.), P.C. (Asian Journal of Chemistry, 2010)
Some 2-arylimino-3-phthalimidoacetyl-4-thiazolidinones and their 5-arylidine derivatives were synthesised and screened for their antifungal activity against Fusarium moniliforme, Aspergillus flavus and Alternaria alternata.